Principles of Drug Dosing in Sustained Low Efficiency Dialysis (SLED) and Review of Antimicrobial Dosing Literature - Paula Brown; Marisa Battistella (MDPI AG, 2020)
The use of sustained low-efficiency dialysis (SLED) as a renal replacement modality has increased in critically ill patients with both acute kidney injury (AKI) and hemodynamic instability. Unfortunately, there is a paucity of data regarding the appropriate dosing of medications for patients undergoing SLED. Dose adjustment in SLED often requires interpretation of pharmacodynamics and pharmacokinetic factors and extrapolation based on dosing recommendations from other modes of renal replacement therapy (RRT). This review summarizes published trials of antimicrobial dose adjustment in SLED and discusses pharmacokinetic considerations specific to medication dosing in SLED. Preliminary recommendation is provided on selection of appropriate dosing for medications where published literature is unavailable.